COMPARISON OF A NEW VERESS NEEDLE ENTRY METHOD AND CLASSIC VERESS NEEDLE ENTRY METHOD IN GYNECOLOGIC LAPAROSCOPY: A PROSPECTIVE RANDOMIZED STUDY - Erkayıran, Uğurkan; Köstü, Bülent; Özer, Alev (International Journal of Research -GRANTHAALAYAH, 2018)
Background: To compare cranial 15º angulation of Veres needle to classic Veress needle entry in closed laparoscopic entry in obese patients. Method: Patients with BMI index>30 were divided into two groups. Initial entry into the abdomen in Group 1 (n=29) was performed with the intraumbilical insertion of Veress needle in 90o angle relative to the horizontal plane. In Group 2 (n=31) the Veress needle was placed intraumbilically in a cranial direction, the tip of the needle towards the thoracic cavity, with an angle of 15o to the horizontal plane. Two groups were compared with respect of the operative outcomes. Results: In Group 2, the mean number of Veress needle entries attempt was significantly lower than Group 1 (p=0.01). Time to insertion of the Veress needle was found to be significantly shorter in Group 2 than in Group 1 (p<0.001). While entry failure occurred in 3 patients in Group 1 (10.3%), no failures were monitored in any patients in Group 2 (p= 0.01). Complication rate was significantly lower in Group 2 than in Group 1 (p= 0.03). Conclusion: Placement of Veress needle intraumbilically in a cranial direction at 15°angle to the horizontal plane increases entry success and reduces complications.